Which patients discontinue? Issues on Levodopa/carbidopa intestinal gel treatment: Italian multicentre survey of 905 patients with long-term follow-up. (May 2017) - Sensi, Mariachiara; Cossu, Giovanni; Mancini, Francesca; Pilleri, Manuela; Zibetti, Maurizio; Modugno, Nicola; Quatrale, Rocco; Tamma, Filippo; Antonini, Angelo; ,
Abstract: Objectives: To report the results of a national survey aimed at quantifying the current level of diffusion of Levodopa/carbidopa intestinal gel (LCIG) in Italy. Methods: Sixty Parkinson's Disease (PD) specialists in Italy were invited to complete a survey covering issues on clinical and practical aspects of LCIG therapy. Results: Clinical features of 905 patients were collected retrospectively. The majority of centres reported the use of a multidisciplinary team, biochemistry testing, neurophysiological and neuropsychological tests before and after treatment, in addition to caregivers' training and patient's follow as outpatients. Most centres (60%) used internal guidelines for patient selection. The overall rate of adverse events was 55.1%. Weight loss, chronic polyneuropathy and stoma infection were the most frequently reported. 40% of centres used replacement therapy with Vitamin B12 and Folic acid from the start of LCIG and continued this for the duration of treatment. The rate of discontinuation was of 25.7% overall, with 9.5% of cases occurring in the first year. The main causes of withdrawal were device-related complications, disease progression (comorbidity, severe dementia) and caregiver and/or patient dissatisfaction. Conclusions: In Italy LCIG infusion is managed in a uniform manner at a clinical, practical and organizational level even though the selection criteria are not standardized through the country. The high percentage of patients remaining on treatment in the short- and long-term follow-up confirms effectiveness of treatment, careful follow-up, and appropriate patient and caregivers training. Highlights: It is a long term follow up on more than 900 levodopa-carbidopa intestinal gel patients. Provides an overview of the causes and rates of withdrawal in the short and long term. Main cause of withdrawal were: device-related complications, disease progression, caregiver/patient's dissatisfaction. The overall rate of discontinuation was of 25.7 %, 9.5 % in the first year post implant.